Engelbecken - Bak, Gamma (Germany : GM films, 2014)
Completed 25 years after the fall of the Wall, this film is a historical document taking us back to the time when the directors, Gamma Bak (West Berlin) and Steffen Reck (East Berlin), had a cross-border relationship. The film brings together personal archival materials, amateur films, and recordings of the theatrical performances of the East Berlin avant-garde theatre group Zinnober of which Steffen Reck was a founding member.
Film also on HDD Verzio11/12 located: M22 R17 S2 R4
Verzio Film Festival Submission